Experimental Study on Physicomechanical Properties of Sandstone under Acidic Environment - Shuguang Li; Runke Huo; Bo Wang; Zhenzhong Ren; Yu Ding; Meiting Qian; Tian Qiu (Advances in Civil Engineering)
The influence of acid solution and immersion time on the physicomechanical properties of sandstone is investigated. Uniaxial compression tests on sandstone samples are conducted to determine the variations of relative mass, deformation, and strength characteristics of sandstone subjected to different pH sulfuric acid corrosion values. The changes of pH and Mg2+ and Ca2+ concentration of immersion solutions are monitored during soaking. The corrosion mechanism of sandstone attacked by the acid solution is discussed with the results of SEM tests. Based on the nondestructive CT scanning test, the damage variables of acid-corroded sandstone are deduced, and the damage degree of sandstone is quantitatively analyzed. The results indicate that the deformation characteristics of sandstone samples under acid attack are characterized by the softening of rock, and the softening degree gradually increases with the increase of the acidity and the soaking time. The peak strength of sandstone samples declines as soaking time extends. The chemical effects lead to a large amount of dissolution of the rock mineral assemblage, resulting in the large-scale development of the pores inside the rock, which changes the macroscopic mechanical properties. The damage variables of acid corrosion sandstone based on CT numbers are deduced, and the quantitative relationship between damage variables and immersion time is established, which provides a basis for constructing a damage constitutive model of sandstone in the acidic environment.